Demand-Side Instruments to Reduce Road Transportation Externalities in the Greater Cairo Metropolitan Area - Parry, Ian W.H.; Timilsina, Govinda R. (Taylor and Francis, 2014)
We estimate efficient prices for passenger transportation in Greater Cairo to address externalities from local pollution, greenhouse gases, traffic congestion, and traffic accidents. An estimated $2.20 per gallon gasoline tax (2006 US$) would be economically efficient, compared with the current subsidy of $1.20 per gallon. Per-mile tolls could target congestion and accident externalities more efficiently than fuel taxes, however. Most efficient is combining a gasoline tax of $0.80 per gallon with per-mile tolls of $0.12 for autos and $0.19 for microbuses. Current public bus and rail fare subsidies are close to efficient levels in the absence of such policies.